Illustrated record of the freshwater copepod Leptodiaptomus dodsoni (Calanoida, Diaptomidae) from central Mexico with comments on the distribution of the genus - Silva-Briano, Marcelo; Suárez-Morales, Eduardo (Biota Neotropica, 2010)
The freshwater planktonic calanoid copepod Leptodiaptomus dodsoni Elías-Gutiérrez, Suárez-Morales & Romano, 1999, a rare species known only from western Mexico, is here recorded from the State of Aguascalientes, central Mexico. This species has a uniquely large, sinuous spine on segment 13 of the right male antennule, reaching the distal margin of segment 15. There are subtle differences between these two known populations; the morphological range of the species is complemented with data from the new specimens. This is the first record of L. dodsoni after its original description; it is probably restricted to a latitudinal fringe in central Mexico. Of the 22 nominal species of Leptodiaptomus currently recognized, up to 7 are known from the Neotropical region and some appear to be true endemics. Apparently, this primarily Nearctic genus radiated in North America and some species reached the Neotropical region where they diversified. A key for the identification of the species of the genus known from the Neotropical region is also provided.